2010
DOI: 10.1101/gad.1915510
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-140 plays dual roles in both cartilage development and homeostasis

Abstract: Osteoarthritis (OA), the most prevalent aging-related joint disease, is characterized by insufficient extracellular matrix synthesis and articular cartilage degradation, mediated by several proteinases, including Adamts-5. miR-140 is one of a very limited number of noncoding microRNAs (miRNAs) specifically expressed in cartilage; however, its role in development and/or tissue maintenance is largely uncharacterized. To examine miR-140 function in tissue development and homeostasis, we generated a mouse line thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
535
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(566 citation statements)
references
References 41 publications
20
535
3
8
Order By: Relevance
“…The results of these studies indicate that miR-140 is one of the main regulators of chondroblast differentiation through its effects on the expression of not only Sox9 (Karlsen et al 2013), but also several other targets (Hdac4, Sp1, Smad3, and aggrecan) (Pais et al 2010, Nakamura et al 2011, Karlsen et al 2013. Moreover, independent groups have developed miR-140-null mice, which displayed a concordant phenotype with major growth defects of endochondral bones (Miyaki et al 2010, Nakamura et al 2011, Papaioannou et al 2013. Interestingly, Sox9, L-Sox5, and Sox6 have been proved to cooperatively activate the miR-140 promoter in vivo and in vitro (Miyaki et al 2010, Yamashita et al 2012, as well as other chondrogenic differentiation-related miRNAs (Guerit et al 2013, Martinez-Sanchez & Murphy 2013.…”
Section: Mirnas and Chondroblast Differentiationmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of these studies indicate that miR-140 is one of the main regulators of chondroblast differentiation through its effects on the expression of not only Sox9 (Karlsen et al 2013), but also several other targets (Hdac4, Sp1, Smad3, and aggrecan) (Pais et al 2010, Nakamura et al 2011, Karlsen et al 2013. Moreover, independent groups have developed miR-140-null mice, which displayed a concordant phenotype with major growth defects of endochondral bones (Miyaki et al 2010, Nakamura et al 2011, Papaioannou et al 2013. Interestingly, Sox9, L-Sox5, and Sox6 have been proved to cooperatively activate the miR-140 promoter in vivo and in vitro (Miyaki et al 2010, Yamashita et al 2012, as well as other chondrogenic differentiation-related miRNAs (Guerit et al 2013, Martinez-Sanchez & Murphy 2013.…”
Section: Mirnas and Chondroblast Differentiationmentioning
confidence: 84%
“…Moreover, independent groups have developed miR-140-null mice, which displayed a concordant phenotype with major growth defects of endochondral bones (Miyaki et al 2010, Nakamura et al 2011, Papaioannou et al 2013. Interestingly, Sox9, L-Sox5, and Sox6 have been proved to cooperatively activate the miR-140 promoter in vivo and in vitro (Miyaki et al 2010, Yamashita et al 2012, as well as other chondrogenic differentiation-related miRNAs (Guerit et al 2013, Martinez-Sanchez & Murphy 2013. miR-181a is highly expressed in chondrocytes, and it has been suggested that it works as a negative feedback system to preserve the homeostasis of cartilage by targeting Ccn1 (Ccna2; which promotes chondrogenesis) and Acan (encoding the protein aggrecan, the major proteoglycan in the cartilage ECM) (Sumiyoshi et al 2013).…”
Section: Mirnas and Chondroblast Differentiationmentioning
confidence: 99%
“…2 Abnormalities in cartilage development have been observed in Dicer gene dysfunction models, and miRNA is known to play a key role in cartilage differentiation. 3 miRNA plays a key role in differentiation and growth in organs and tissues, 2 and miRNAs expressed specifically in cartilage [4][5][6][7][8] have been reported. Till date, miR21, 4 miR22, 9 miR27a, 6 miR140, 10 and miR146 8 have been reported as miRNAs that are associated with cartilage metabolism.…”
mentioning
confidence: 99%
“…miRs also serve crucial roles in cell proliferation, apoptosis and differentiation (15 is regulated by miRs in humans (16). Furthermore, a number of studies have demonstrated that miR is not only involved in the regulation of cartilage development, but also serves pivotal roles in the pathogenesis of the nucleus pulposus degeneration and arthritis (17,18). However, it remains unknown whether miR is associated with the molecular mechanism of CEP degeneration.…”
Section: Introductionmentioning
confidence: 99%